Problematyka oceny controllingu w polskich przedsiębiorstwach - Nowosielski, Krzysztof (Estimation of Controlling in Polish Enterprises, 2005)
In the article initiative results of research concerning estimation of controlling in Polish enterprises are presented. The author's intention is to collect opinions of managers on relevance of controlling estimation. In the second place respondents were asked for criteria which should be included in this kind of estimation. Information gathered in the research confirms usefulness of such a topic and it is premise to take up the discussion on effectiveness of controlling in the future.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 283-290